Medial entorhinal VIP-expressing interneurons receive input from the thalamic anterior dorsal nucleus and are critical for spatial memory - Marie Oulé; Saishree Badrinarayanan; Rosa Sundar-Maccagno; Mark P. Brandon (Proceedings of the National Academy of Sciences, 2025)
Vasoactive intestinal peptide (VIP) cells have emerged as a crucial component of the inhibitory network, facilitating interregional communication, particularly in the context of associative memory. To expand our current understanding of the role of this population, we combine anatomical and functional approaches to question the influence of VIP cells in the medial entorhinal cortex (MEC), a region key for navigation and spatial memory. From our anatomical tracing study, our findings reveal that neurons located in the anterodorsal thalamic nucleus (ADN) specifically project onto MEC interneurons, with a strong preference for MEC VIP cells. Additionally, MEC VIP cells receive input from the hippocampus, the subicular complex, and the retrosplenial cortex, suggesting a specialized role for MEC VIP cells in spatial memory. Indeed, we find that MEC VIP cells exhibit increased c-Fos expression in a spatial memory task and show that chemogenetic inhibition of these neurons impairs task performance. Together, these data reveal a specific projection of head-direction (HD) information onto MEC interneurons and confirm that MEC VIP-expressing cells play a critical role in spatial memory.